The ANALYSIS OF INCREASED SOCIAL INTERACTION THROUGH TRADITIONAL SPORTS GAMES IN ELEMENTARY SCHOOL STUDENTS - Mulyani, Tresna; Kurniawati, Ani; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi (STKIP Muhammadiyah Kuningan, 2024)
Physical education is one of the subjects in schools, including elementary schools. Learning to swim is not easy as experienced by 6th grade students of SDN 2 Pataruman Garut. Where they still have a lot of difficulty in doing social interactions. One of the learning methods that can be used in this case is the Direct Instruction (DI) method with a Video Media approach and game application. This study aims to determine the effect in improving the results of social interaction through traditional sports on 6th grade students of SDN 2 Pataruman Garut. Direct learning method assisted by video media, is very good for improving the results of students' social interaction quite significantly. From the results of the analysis obtained a significant increase from cycle 1, cycle 2 and cycle 3. The results of social interaction through traditional sports in cycle 1 in the Good category were 8% the number of students who completed was 15 students. In cycle 2 there was an increase in the percentage of students' social interactions in the Good category by 40%, while 23 students were complete. In cycle 3, there was an increase in students' social interactions in the good category by 64% while 24 out of 25 students were complete